Bird Communities in Coastal Areas. Effects of Anthropogenic Influences and Distance From the Coast - Graells, Giorgia; Celis-Diez, Juan L.; Corcoran, Derek; Gelcich, Stefan (Frontiers in Ecology and Evolution, 2022)
Urbanization effects have been studied all over the world, documenting impact in species richness, abundances and changes in species communities. Birds have been broadly used as study models. In general, urbanization affects birds, reducing species richness, especially in the urban core, and increasing species richness in areas with intermediate levels of disturbance, such as suburbs. Urbanization also changes species assemblages depending on urban characteristics and resources available, creating habitats for different species. Even when more than half of the cities in the world are on the coast, the effects of urbanization on habitat use of terrestrial and marine birds in coastal urban environments has received little attention. We hypothesized that coastal cities would present different bird diversity in modified marine areas and modified inland areas because in the first urban, terrestrial and marine ecosystems coexist. Here, we predict that modified marine areas will have higher species richness than modified inland areas and natural marine areas. For bird assemblages, we expect to find similar species compositions between sites with similar habitat characteristics more than closeness. We compare habitat use of marine and terrestrial avifauna in the human-modified coastal city of Valparaiso, Chile, characterized by a range of urban developments within city boundaries. We specifically compare corrected bird abundance in six different possible habitats for birds, according to distance to the coast, and human influence. Bird counts (50 m fixed radius) were conducted in winter and spring of 2019. Bird species richness and abundances, corrected by the probability of detection, were estimated. Additionally, species composition and occupancy of bird species in those habitats were calculated. Results show that coastal urban cities can provide different habitats for bird species. Modified inland habitats differ from semi-natural inland habitats and from the modified beaches in species richness and species composition. Environmental heterogeneity presented in coastal cities seems to allow the coexistence of marine and terrestrial bird species, showing differences in species richness and bird assemblages for marine-inland environments and natural- modified habitats. Results highlight the need to consider these factors for urban planning in order to conserve bird diversity in coastal urban areas.